2019
DOI: 10.1111/cid.12873
|View full text |Cite
|
Sign up to set email alerts
|

Platform‐switched implants vs platform‐matched implants placed in different implant‐abutment interface positions: A prospective randomized clinical and microbiological study

Abstract: Background Placement of the implant‐abutment interface (IAI) away from the bone crest has been suggested to have positive impacts on maintenance of peri‐implant tissues. Purpose To assess the effects of platform‐switched and platform‐matched implants, taking into consideration the IAI at different positions relative to the bone crest, on clinical, radiographic, and microbiological outcomes during 12 months following functional loading. Materials and Methods The present prospective randomized study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Therefore, in this study, cases involving severe bone resorption and difficulties in distinguishing between the implant platform and the bone crest were excluded, and the alveolar bone width at 1 mm below the crest level was measured as the coronal third to reduce measurement errors. However, several studies have reported marginal bone loss around dental implants at the crest level [ 30 , 31 ]. Therefore, although the present study could accurately and clearly determine the alveolar bone width at the crest level, the resorption of coronal bone width around implants might be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, cases involving severe bone resorption and difficulties in distinguishing between the implant platform and the bone crest were excluded, and the alveolar bone width at 1 mm below the crest level was measured as the coronal third to reduce measurement errors. However, several studies have reported marginal bone loss around dental implants at the crest level [ 30 , 31 ]. Therefore, although the present study could accurately and clearly determine the alveolar bone width at the crest level, the resorption of coronal bone width around implants might be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The number of samples of implants with prosthetic platform change (PS) and without prosthetic platform change (PM) of the included studies was similar in all of them, the total implants samples being 475 and 462, respectively. The most disparate study in this regard had a sample size of 45 (PS)/25 (PM) [ 11 ]. All these data are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the surgical procedure and flap design, Fernández et al [ 16 ] did not convey this information. Thus, of the remaining eight studies, all of them performed a full-thickness flap, which was subsequently closed in two studies until prosthetic restoration [ 11 ] or until an exposed healing abutment was added 8 weeks after surgery [ 15 ]. In the remaining six studies, the flap was sutured around an exposed healing abutment that modified the gingival profile of the implant until the time of prosthetic restoration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated a favorable effect of PS, presenting crestal bone gains between 0.3 and 0.9 mm compared to platform-matching (Cappiello et al, 2008;Chrcanovic et al, 2015;Maeda et al, 2007;Telleman et al, 2014). According to the findings of Uraz et al (2020) and Lago et al (2017), PS implants inserted at the crestal level also presented low bacterial load and adequate soft tissue healing.…”
Section: Discussionmentioning
confidence: 99%